New light on ω-3 polyunsaturated fatty acids and diabetes debate: a population pharmacokinetic-pharmacodynamic modelling and intake threshold study - Wang, Ling; Huang, Xiaomin; Sun, Mingyao; Zheng, Tian; Zheng, Luyan; Lin, Xiaolan; Ruan, Junshan; Lin, Fan (Nutrition & diabetes, 2024)
Objective ω-3 polyunsaturated fatty acids (PUFA) are a key modifiable factor in the intervention of type 2 diabetes, yet recommendations for dietary consumption of ω-3 PUFA in type 2 diabetes remain ambiguous and controversial. Here, we revisit the subject in the light of population pharmacokinetic-pharmacodynamic (PPK-PD) modeling and propose a threshold for intake. Research design and methods Plasma levels of ω-3 PUFA and glycosylated hemoglobin (HbA 1c ) were measured as pharmacokinetic and pharmacodynamic indicator, respectively. The nonlinear mixed effect analysis was used to construct a PPK-PD model for ω-3 PUFA and to quantify the effects of FADS gene polymorphism, age, liver and kidney function, and other covariables. Results Data from 161 patients with type 2 diabetes in the community were modeled in a two-compartment model with primary elimination, and HDL was a statistically significant covariate. The simulation results showed that HbA 1c showed a dose-dependent decrease of ω-3 PUFA plasma level. A daily intake of ω-3 PUFA at 0.4 g was sufficient to achieve an HbA 1c level of 7% in more than 95% of patients. Conclusions PPK/PD modeling was proposed as a multilevel analytical framework to quantitatively investigate finer aspects of the complex relationship between ω-3 PUFA and type 2 diabetes on genetic and non-genetic influence factors. The results support a beneficial role for ω-3 PUFA in type 2 diabetes and suggested the intake threshold. This new approach may provide insights into the interaction of the two and an understanding of the context in which changes occur.